Analisis Yuridis Undang-Undang Penistaan Agama Dalam Hukum Islam - Rahmad Haniru; La Jidi; Abdul Nowi; Safaruddin Yahya (Journal on Education, 2024)
This research aims to analyze the juridical law of deviant acts such as blasphemy against religion. It is important to pay attention, because religion is a sacred belief that should not be insulted or demeaned. Article 29 of the Constitution of the Republic of Indonesia states that "the Indonesian state is based on the one and only God. The research study method used in this research is a qualitative library research method. The research technique here is to use the library research method, which is carried out by searching for research data or information through reading, be it books, journals or others. The results of this research show that the law on religious blasphemy in Indonesia is determined based on law, presidential decrees and ministerial regulations. In Article 156 (a) of the Criminal Code, it is stated that every person who deliberately expresses feelings in public or commits acts that are hostile to, abuses or desecrates a religion adhered to in Indonesia or with the intention of causing people not to adhere to any religion. Those who violate this article will be subject to a maximum prison sentence of five years. In an Islamic perspective, blasphemy against the Islamic religion is like denouncing or insulting the Koran and hadith, leaving or ignoring what they contain, and turning away from the laws contained in the Koran and hadith or like teaching a heretical sect. or claiming to receive revelations or claiming to be a prophet, is certainly very contrary to the true teachings of Islam.